Application of Statistics in Establishing Diagnostic Certainty - Denegar, Craig R. (The National Athletic Trainers' Association, Inc, 2012)
The examination and assessment of injured and ill patients leads to the establishment of a diagnosis. However, the tests and procedures used in health care, including procedures performed by certified athletic trainers, are individually and collectively imperfect in confirming or ruling out a condition of concern. Thus, research into the utility of diagnostic tests is needed to identify the procedures that are most helpful and to indicate the confidence one should place in the results of the test. The purpose of this report is to provide an overview of selected statistical procedures and the interpretation of data appropriate for assessing the utility of diagnostic tests with dichotomous (positive or negative) outcomes, with particular attention to the interpretation of sensitivity and specificity estimates and the reporting of confidence intervals around likelihood ratio estimates.